Penerapan Metode Analytical Hierarchy Process (AHP) Sebagai Pendukung Keputusan dalam Menentukan Internet Service Provider Terbaik di Pangkalpinang - Yogi Prihartono; Hilyah Magdalena (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2016)
Internet service provider used in today's rapidly growing with a wide selection of advantages and disadvantages. Because it was so many criteria - criteria that can be used as a basic internet service providers the most suitable to be applied in the agency in Pangkalpinang. In this study, the authors raise some of the network providers are XL, Telkomsel, Indosat, Three and Smartfren. To select an Internet service provider with a six-level criteria. The level 1 criteria: ease of users, ease of use, speed of data transfer, type of service, access restrictions internrt / quota, network level, and the type of card, level 2 criteria consists of 20 criteria derived from special advantages to the internet service provider. As for the level 3 there are five alternatives are XL, Telkomsel, Indosat, Three and Smartfren. The results of this election result as an internet service provider XL is best as compared with Telkomsel, Indosat, Three, and Smaertfren. XL reliability levels reached 31.7%. And the most influential factor in the selection process is the data transfer speed factor reached 32.5%.